Optimization of Coagulation–Flocculation Treatment for Peat Water Based on Physicochemical Characteristics - Rio Agustian Siregar; R Mohammad Alghaf Dienullah; Aulia Ulfah Farahdiba (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Peat water is characterized by low pH and high concentrations of dissolved organic matter, limiting its direct use as a clean water source. This study aimed to determine the optimum dosages of Poly Aluminium Chloride (PAC) and hydrated lime (Ca(OH)?) for peat water treatment based on physicochemical characteristics. The study employed a laboratory-scale jar test with rapid mixing at 120 rpm, followed by slow mixing at 45 rpm, using various dosages of PAC and hydrated lime. The treatment performance was evaluated based on pH, total dissolved solids (TDS), electrical conductivity, and salinity. The results demonstrated that the combination of PAC and hydrated lime significantly improved the physicochemical characteristics of peat water. The optimum dosage yielded pH values near the recommended range while maintaining acceptable TDS, electrical conductivity, and salinity. These findings indicate that the combined application of PAC and hydrated lime is an effective alternative for improving peat water quality and can serve as a reference for peat water treatment systems Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable cities and communities